2002
DOI: 10.1007/s00415-002-0775-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between urinary symptoms and disease-related parameters in multiple sclerosis

Abstract: Urinary symptoms, especially irritative symptoms, reflect the condition of the disease. Thus, the quantified urinary symptoms may assist neurological diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 29 publications
(74 reference statements)
6
32
0
Order By: Relevance
“…Similarly, in a prospective study of symptomatic MS patients, no significant correlation was found between clinical features and urodynamic patterns [5]. Instead, Betts et al showed that MS patients with irritative bladder symptoms and lower limb pyramidal involvement were highly likely to have detrusor hyperreflexia, such as to make unnecessary to run the urodynamic study to choose the anticholinergic therapy [7]; similarly Araki et al found that urinary irritative symptoms reflect the disease severity [9]. Betts et al reported a linear progression of residual urine volume with bladder FS score, and suggested to perform the post-void urine volume measurement only in patients with significant disability [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in a prospective study of symptomatic MS patients, no significant correlation was found between clinical features and urodynamic patterns [5]. Instead, Betts et al showed that MS patients with irritative bladder symptoms and lower limb pyramidal involvement were highly likely to have detrusor hyperreflexia, such as to make unnecessary to run the urodynamic study to choose the anticholinergic therapy [7]; similarly Araki et al found that urinary irritative symptoms reflect the disease severity [9]. Betts et al reported a linear progression of residual urine volume with bladder FS score, and suggested to perform the post-void urine volume measurement only in patients with significant disability [7].…”
Section: Discussionmentioning
confidence: 99%
“…Few and heterogeneous studies have investigated the relationship between subjective urinary complaints and objective urological parameters in MS patients, reaching different conclusions [3,[5][6][7][8][9]. Is a routinary evaluation of urinary symptoms sufficient to exclude the presence of bladder dysfunction in patients with MS?…”
Section: Introductionmentioning
confidence: 99%
“…Therefore we could also speculate that pathomechanisms of spastic paraparesis might be applied to bladder smooth muscle, which result in DHIC. With regard to multiple sclerosis, several reports revealed that many patients show both storage and voiding symptoms and urinary symptoms correlated with disease severities [Ciancio et al, 2001;Araki et al, 2002]. Araki et al [2002] showed that among the lesions in the central nervous system, only the presence of a spinal cord lesion was related to the degree of urinary symptoms.Therefore, DHIC in multiple sclerosis might be caused by mechanisms similar to those occurring in spinal cord lesions.…”
Section: Discussionmentioning
confidence: 99%
“…1 Storage symptoms correlate well with the Expanded Disability Status Scale (EDSS) 9 and pyramidal tract involvement; however, their association with voiding symptoms is much weaker. 10 LUTS in MS may be influenced by gender and age. While their exact impact on patient symptoms has not been thoroughly investigated, cumulative action of other diseases is possible, eliciting bladder dysfunction -benign prostate obstruction, pelvic relaxation, or stress urinary incontinence (SUI).…”
Section: Prevalence Of Luts In Msmentioning
confidence: 99%